Traumatic Mucormycosis of Auricular Cartilage in an Iranian Diabetic Patient - Meidani, Mohsen (Int Med Case Rep J, 2020)
Mucormycosis is an uncommon and acute fungal infection, with high morbidity and mortality. Traumatic mucormycosis mainly occurs in military conflicts, civilian trauma, and vehicle accidents. Hurricanes, tornadoes, floods, and tsunamis also play a major role in causing mucormycosis by inoculation. Herein, we presented a case of trauma-related mucormycosis in a 70-year-old diabetic male. He referred to a specialty clinic due to the auricular swelling after having fallen and having a major trauma in his ear. Pathologic examination of necrotic cartilage revealed broad ribbon like aseptate hyphae. Antifungal therapy with amphotericin B deoxycholate (1.5 mg/kg/day) was administered for 6 weeks as an initial therapy, and the patient was discharged with a regimen of posaconazole oral solution (400 mg PO bid with meals) for 8 weeks. He followed up for one year and there was no recurrence of the infection. In conclusion, traumatic mucormycosis is a rare but potentially life-threatening fungal infection. Early diagnosis and surgical excision are essential regarding the management of this critical condition. Knowing the underlying diseases is preferable to early diagnosis and timely initiation of antifungal therapy in order to improve survival rates.